Clima e doenças tropicais negligenciadas no espaço urbano de Aracaju/SE - Santos, Fernanda Flores Silva dos (2022)
The concern about the health-disease duality of man is historically old. The link between climate and health dates back to classical antiquity and has evolved scientifically according to the time and space analyzed. As a result of a new condition of urbanized society intensified throughout the twentieth century, adding changes in atmospheric characteristics, the interaction between climate and society has become more notorious. In this perspective, the research aimed to analyze the occurrence and distribution of Leptospirosis and dengue cases in the urban space of Aracaju, taking into consideration the climatic aspects and the intervening socio-environmental factors in the period 2000 to 2019. To fulfill the objectives in the course of the investigation, the General Systems Theory was used as a method of approach, articulated with the Rhythmic Analysis model developed by Monteiro (1976). The methodological procedures in distinct phases were based on incidence, statistical techniques of correlation (r), Kernel density estimator and synthesis indicators of socio-environmental vulnerability, enabling, through Digital Cartography, the spatialization in thematic maps of the diseases confirmed by the Sistema de Informação de Agravos de Notificações (SINAN). Among other results, an increase in cases of Leptospirosis was observed in the autumn/winter period, in the months of April, June and July, considered the rainiest, especially due to the propagation of the Atlantic Polar Front and other atmospheric systems that exert direct action on the coastal coast of Aracaju. Although the climatological influence has been perceptible, the socioeconomic factor in the classified risk zones proved to be one of the most preponderant in the spatial configuration of the disease. In the case of dengue, the incidence relationship was not so clear, since the areas of highest epidemiological risk did not always culminate in the highest occurrences of the disease, showing that socio-environmental factors had a weight on the incidences, but were not determinant. From the climatic point of view, it was found that Aracaju has favorable conditions throughout the year for the spread of these waterborne diseases, because statistically there was a moderate to strong correlation between climatic elements and occurrences for both Leptospirosis and dengue. It is concluded, therefore, that the socio-environmental conditions of the diseases can serve as a contribution to the planning of public policies in order to perform preventive actions considering the existing risk factors in the urban space of Aracaju that favor the spread of diseases and that are unequal, affecting in different proportions the health of citizens.